Pathology of Vascular Skin Lesions Clinicopathologic Correlations - Sangüeza, Omar P.; Requena, Luis (Humana Press, 2003)
Cutaneous vascular proliferations are exceedingly common, and with the recent identification of new diseases, their diagnosis, classification, and treatment can be complicated. In Pathology of Vascular Skin Lesions: Clinicopathologic Correlations, Omar P. Sangüeza, md, and Luis Requena, md, review in detail all the vascular proliferations involving the skin and subcutaneous tissue, including recently described disease entities. Superbly illustrated with both clinical and histopathologic photographs, the book moves from a proposed new system of classification and nomenclature for vascular neoplasms, to a full discussion of benign and malignant proliferations, including hamartomas, benign neoplasms, and several newly reported related diseases. The authors provide an in-depth description of the clinical and morphologic aspects of each entity and detail their clinicopathologic correlation, differential diagnosis, prognosis, and therapy. Additional chapters outline the normal embryology, histology, and anatomy of skin vasculature, as well as the use of special techniques for the study of vascular proliferations. Comprehensive and practical, Pathology of Vascular Skin Lesions: Clinicopathologic Correlations provides dermatologists, pathologists, and skin researchers with a complete, authoritative guide to the diagnosis and treatment of vascular proliferations of the skin, all generously illustrated with a wide-ranging array of clinical cases and histopathologic specimens
Keywords: Pathology